2013
DOI: 10.4161/epi.26842
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of miR-21 in colorectal cancer

Abstract: Previous studies have uncovered several transcription factors that determine biological alterations in tumor cells to execute the invasion-metastasis cascade, including the epithelial-mesenchymal transition (EMT). We sought to investigate the role of miR-21 in colorectal cancer regulation. For this purpose, miR-21 expression was quantified in a panel of colorectal cancer cell lines and clinical specimens. High expression was found in cell lines with EMT properties and in the vast majority of human tumor specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(47 citation statements)
references
References 66 publications
2
42
3
Order By: Relevance
“…However, there has not been ample research conducted on the impact of miRNA-21 and EMT in CRC. Three studies observed high expression levels of miRNA-21 in cancers with up-regulated mesenchymal (snail-1, N-cadherin and vimentin) and down-regulated epithelial (E-cadherin) markers 12 13 20 26 30. Our data, however, indicated high expression levels of miRNA-21 in cancers with high E-cadherin expression and negative snail-1 expression.…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…However, there has not been ample research conducted on the impact of miRNA-21 and EMT in CRC. Three studies observed high expression levels of miRNA-21 in cancers with up-regulated mesenchymal (snail-1, N-cadherin and vimentin) and down-regulated epithelial (E-cadherin) markers 12 13 20 26 30. Our data, however, indicated high expression levels of miRNA-21 in cancers with high E-cadherin expression and negative snail-1 expression.…”
Section: Discussioncontrasting
confidence: 62%
“…MiRNA-21 high expression levels have also been associated with poor disease survival in colorectal, breast, pancreatic, cervical and lung cancers 19 24. These studies, therefore, suggested that miRNA-21 may be used as a marker of prognosis 12 25–27…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations